The bamA gene for anaerobic ring fission is widely distributed in the environment - Porter, Abigail W.; Young, Lily Y. (Frontiers in Microbiology, 2013)
Aromatic compounds are a major component of the global carbon pool, and include a diverse range of compounds such as humic acid, lignin, amino acids, and industrial chemicals. Due to the prevalence of aromatic compounds in the environment, microorganisms have evolved mechanisms to metabolize that available carbon. While anaerobic monoaromatic degradation can be initiated in a number of different ways, the signature central metabolite for these pathways is benzoyl-CoA. Aromatic chemicals with different upstream degradation pathways all funnel into the downstream benzoyl-CoA pathway. Different genes encoding enzymes of the benzoyl-CoA pathway could be used as biomarkers, however the ring opening hydrolase, encoded by the bamA gene, is ideal because it is detected under a range of respiratory conditions, including denitrifying, iron-reducing, sulfate-reducing, and fermentative conditions. In this work we evaluated a number of DNA samples from diverse environments for the presence of the bamA gene, and had positive results for every sample. We further explored the bamA gene diversity in six of these sites as compared to published genome sequences and found that our clones were distributed throughout the dendrogram, although there were clone sequences from two sites that formed a unique clade. When we used a functional operational taxonomic unit based clustering analysis to compare the diversity of our sites to several locations reported in the literature, we found that there were two clusters of sites, and benzene contaminated sites were present in both clusters. Given the number of potential upstream inputs from natural and manmade monoaromatic compounds, the benzoyl-CoA pathway and the bamA gene play an important role in the global carbon cycle that has thus far been understudied.